The Influence of Recruitment and Training on Employee Performance through Job Satisfaction as an Intervening Variable at PT. XYZ in Riau - Fabelia Regina Cahyani; Trias Setiawati; Andriyastuti Suratman (Dinasti Publisher, 2025)
This research is entitled